Foster a cyberstar WeChat public account-"Cats Come" - Wang, Yangwen, 1974- (SAGE Business Cases., 2018)
The case describes how the WeChat public account "Cats Come" has been fostered into a cyberstar. In the Web 2.0 era, new media led by WeChat and microblogging have gradually become the mainstream way to disseminate information and attract followers. Issues related to the operation of new media accounts, such as how to win amid fierce competition, how to provide values for followers, how to promote brand IP, and how to develop core competence, are worth studying. The WeChat public account "Cats Come" has provided a typical case to find out the answers. Taking "Cats Come" as an example, we analyze the process in which a public account positions itself accurately amid fierce competition, meets customers' demands continuously, and then develops and establishes its own core competence.